Clinical practice Identifying and treating necrotising fasciitis: a clinical challenge. Issue 4 (2019) - Iacopi, Elisabetta; Riitano, Nicola; Barone, Sara; Abbruzzese, Lorenza; Pieruzzi, Letizia; Goretti, Chiara; Piaggesi, Alberto
No abstract available